A Retrospective of Prevalence of Drugs of Abuse by Hair Analysis in Shanghai using LC–MS-MS. Issue 5 (4th February 2020) - Wang, Xin; Cui, Jingjing; Zhuo, Yue; Shen, Baohua; Zhang, Sujing; Liu, Wei; Shen, Min; Xiang, Ping
Abstract: This study presents a retrospective analysis of the prevalence of drug abuse in Shanghai by hair analysis. Files and toxicology analysis results of a total of 5, 610 cases requesting for hair analysis of abused drugs at the Academy of Forensic Science (AFS) in Shanghai over 12 months between August 2018 and July 2019 were reviewed. All cases of drug abuse identified by hair analysis were from the public security organs in Shanghai, China. Hair samples were analyzed for drugs of abuse and related metabolites, mainly including amphetamine (AMP), methamphetamine (MA), 3, 4-methylenedioxymethamphetamine (MDMA), 3, 4-methylenedioxyamphetamine (MDA), tetrahydrocannabinol (THC), ketamine (K), norketamine (NK), cocaine (COC), benzoylecgonine, morphine, 6-acetylmorphine, flunitrazepam, and 5-methoxy- N, N -diisopropyltryptamine (5-MeO-DIPT), using liquid chromatography–tandem mass spectrometry (LC–MS-MS). Among the 5, 610 cases, 1, 713 (30.5%) were positive for drugs of abuse, with amphetamine-type stimulants (ATS) (57%), including amphetamines (AMP and MA) (48%), MDMA and MDA (9%), being the most frequently detected drugs, followed by THC (14%), COC (8%), 5-MeO-DIPT (8%), and K (7%). The majority (75%) of positive hair samples were from male subjects. Overall, 77% of abusers were younger than 44 years old. The proportion of female subjects (22.3%) under 24 years was larger than that of male subjects (7.8%). There were 132 cases (7.7%) in which more than one type of drug was detected among 1, 713 drug-positive cases. The most common combination was MDMA and K. The present study characterizes the current toxicological profile of drug abuse cases and provides a scientific basis for drug abuse prevention. Moreover, the hair concentration distributions of the commonly abused drugs in positive cases have been reported.